2008
DOI: 10.1002/ptr.2411
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antileukaemic activity of extracts from chokeberry (Aronia melanocarpa [Michx] Elliott) and mulberry (Morus alba L.) leaves against sensitive and multidrug resistant HL60 cells

Abstract: The aim of the present study was to determine in vitro antileukaemic activities of extracts obtained from chokeberry (Aronia melanocarpa [Michx] Elliot) and mulberry (Morus alba L.) leaves against promyelocytic HL60 cell line and its multidrug resistant sublines exhibiting two different MDR phenotypes: HL60/VINC (overexpressing P-glycoprotein) and HL60/DOX (overexpressing MRP1 protein). It was found that the extracts from chokeberry and mulberry leaves were active against the sensitive leukaemic cell line HL60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 28 publications
6
34
0
1
Order By: Relevance
“…It has been proven that chokeberry leaves (Aronia melanocarpa) extracts inhibit lipid and protein peroxidation in the brain of rats treated with oxidative stress-inducing factors (Cuvorova, Davydov, Prozorovskii, & Shvets, 2005). Skupień et al (2008) described antileukaemic activity of chokeberry leaves against human promyelocytes of several cell lines (HL60, HL60/ VINC and HL60/DOC), while Maslov et al (2002) in a rat study revealed their antidiabetic properties.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been proven that chokeberry leaves (Aronia melanocarpa) extracts inhibit lipid and protein peroxidation in the brain of rats treated with oxidative stress-inducing factors (Cuvorova, Davydov, Prozorovskii, & Shvets, 2005). Skupień et al (2008) described antileukaemic activity of chokeberry leaves against human promyelocytes of several cell lines (HL60, HL60/ VINC and HL60/DOC), while Maslov et al (2002) in a rat study revealed their antidiabetic properties.…”
Section: Introductionmentioning
confidence: 96%
“…As some studies show, leaves of well-known crops and wild growing plants (such as blackcurrant, chokeberry and bilberry) are a valuable source of antioxidant substances, especially polyphenols (Skupień , Kostrzewa-Nowak, Oszmiań ski, & Tarasiuk, 2008;Tabart et al, 2007;Witzell, Gref, & Näsholm, 2003). It has been proven that chokeberry leaves (Aronia melanocarpa) extracts inhibit lipid and protein peroxidation in the brain of rats treated with oxidative stress-inducing factors (Cuvorova, Davydov, Prozorovskii, & Shvets, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…They are excellent as free radical scavengers including those in the form of the reactive forms of oxygen [Pajk et al, 2006;Skupień et al, 2008]. The radicals are the products of metabolic reactions within the living organism and are also formed in the external medium, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…8 Also, Skupien et al reported that M. alba leaf extract has cytotoxic effect both human leukaemic cell line (HL60) and its multidrug resistant sublines. 31 Some researches now focus on the bioactive components of mulberry and concordantly Dat et al reported 11 flavonoids from the methanol extract of M. alba leaves, which were cytotoxic to HeLa, MCF-7, and Hep3B cancer cells. 32 Interestingly, synergistic cytotoxic effect of a natural compound may not observed when its purified polyphenolic compounds were used.…”
Section: Discussionmentioning
confidence: 92%